IMPLEMENTATION OF THE SIMPLE ADDITIVE WEIGHTING (SAW) METHOD IN THE DECISION SUPPORT SYSTEM FOR DETERMINING SCHOLARSHIPS FOR STUDENTS AT THE STIEKOM NORTH SUMATRA EDUCATION FOUNDATION - Karo Karo, Siddik; Prayogi, Satria Yudha; Tampubolon, Kennedi; Limbong, Riswan; Tamba, RL. Harmady (Cattleya Darmaya Fortuna, 2024)
The allocation of scholarships is a crucial process in educational institutions, aiming to provide financial support to deserving students based on specific criteria. This research explores the implementation of the Simple Additive Weighting (SAW) method within a Decision Support System (DSS) designed to aid in the determination of scholarship recipients at the STIEKOM North Sumatra Education Foundation. The SAW method, known for its simplicity and effectiveness, facilitates the evaluation of multiple criteria by assigning weights to each criterion and calculating a weighted sum for each candidate. This study outlines the development and application of the DSS, focusing on its ability to enhance decision-making accuracy and efficiency in the scholarship awarding process. Through a series of simulations and real-case applications, the system's performance is analyzed, demonstrating its potential to improve transparency and fairness in scholarship distribution. The findings suggest that the SAW-based DSS can serve as a reliable tool for educational institutions in managing scholarship allocations, ensuring that the most qualified students are selected based on a comprehensive evaluation of their academic performance, financial need, and other relevant criteria.